An investigation of factors contributing towards failure or success of implemented EWB-USA water-well borehole projects. Issue 2 (17th February 2021) - Kristoffersen, Andreas; Knight, Joshua N.
ABSTRACT: This paper investigates 90 different factors contributing towards the success of Engineers Without Borders USA water-well borehole projects based on four indicators. Seventy-five per cent of the 22 well projects studied were successful according to at least three of the four success definitions. Different factors impact the success indicators in complex ways. Community engagement should be sought out, though not necessarily during implementation. An experienced travel team, surprisingly, tends to create less successful projects, but this is improved by performing periodic control checks or supplementary pre-implementation surveys.